1978
DOI: 10.1002/ana.410040112
|View full text |Cite
|
Sign up to set email alerts
|

Predictive control of eye movements in parkinson disease

Abstract: Four parkinsonian patients who had shown evidence of an impairment of predictive manual control and 4 age-matched normal subjects were tested for the predictive control of eye movements. Subjects tracked a target with their eyes as it moved in either irregular "noise" or regular (predictable) linear ramp or sine waveforms. Eye movements were monitored by electrooculography, and the overall tracking time lag for each condition was determined by cross-correlation. Both normal and parkinsonian subjects showed pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Our patients were obviously able to extract information about future target movement from the static visual cue. This finding resembles prior observations showing that parkinsonian patients can predictively induce smooth pursuit movements on the basis of temporal information acquired during antecedent trials [13]. However, the patients in the present study showed a major deficit with the accurate timing of the movement onset, which was significantly later than that of the controls but still earlier than without the street.…”
Section: Discussionsupporting
confidence: 89%
“…Our patients were obviously able to extract information about future target movement from the static visual cue. This finding resembles prior observations showing that parkinsonian patients can predictively induce smooth pursuit movements on the basis of temporal information acquired during antecedent trials [13]. However, the patients in the present study showed a major deficit with the accurate timing of the movement onset, which was significantly later than that of the controls but still earlier than without the street.…”
Section: Discussionsupporting
confidence: 89%
“…This distinguishes them from other parkinsonian syndromes (e.g., multisystem atrophy or genetic Parkinson syndromes) 17, 18. Predictive smooth pursuit responses were found to be intact, even in those PD patients who showed a loss of predictive control in manual tasks5 or a deficient capacity of generating anticipatory saccades 6…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is not quite known whether PD patients are capable of (1) anticipating future events before an external trigger appears (i.e., anticipation) and (2) predicting movement velocity once the moving target shortly disappears from the visual scene (i.e., prediction). Previous studies suggested that PD patients are able to predict forthcoming smooth pursuit velocity on the basis of temporal information acquired during ongoing pursuit or antecedent trials 5–8. However, predictive smooth pursuit in PD patients in the latter studies has only been studied by latency and phase‐lag analysis of sinusoidal pursuit or pursuit ramp recordings.…”
mentioning
confidence: 99%
“…Inferences of prediction in the pursuit eye movements of Parkinson’s disease have been based mostly on changes in phase error. In a study of predictive ability in patients with Parkinson’s disease, Flowers23 and Flowers and Downing24 suggested that although these patients showed evidence of impaired predictive control in a manual task, their predictor mechanism for the control of smooth pursuit eye movements was intact. In another study, Bronstein and Kennard10 found no impairment of prediction in the smooth pursuit system of Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%